World Englishes, translingualism, and racialization in the US college composition classroom. Issue 2 (20th February 2020) - Lee, Eunjeong; Alvarez, Sara P.
Abstract: This paper examines the connection between language ownership and racialization as discussed in world Englishes (WE) and translingualism. WE and translingualism have expanded both epistemological and ontological spectrums in understanding how Englishes have been used, understood, and transformed in different global contexts, challenging a monolingual orientation to language and literacy. Yet, less questioned is how the very approach to various ways of 'owning' Englishes contributes to WE and translingualism's work of linguistic justice. In this regard, we argue that the issue of racialization needs to be foregrounded in these two bodies of scholarship to better account for racialized students' language practices and ownership. Situating this examination in the US college composition classroom, we discuss how the conceptualization of language ownership can extend monolingual and racializing ideologies. We conclude by calling for a more linguistically just view of language ownership as a way to undo the racial‐linguistic stratification in educational contexts such as the writing classroom.